2007
DOI: 10.1152/ajpcell.00089.2007
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological properties of human adipose tissue-derived stem cells

Abstract: Human adipose tissue-derived stem cells (hASCs) represent a potentially valuable cell source for clinical therapeutic applications. The present study was designed to investigate properties of ionic channel currents present in undifferentiated hASCs and their impact on hASCs proliferation. The functional ion channels in hASCs were analyzed by whole-cell patch-clamp recording and their mRNA expression levels detected by RT-PCR. Four types of ion channels were found to be present in hASCs: most of the hASCs (73%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
65
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 56 publications
(57 reference statements)
8
65
0
Order By: Relevance
“…Many subsequent studies have demonstrated that, umbilical cord and heart derived MSCs expressed identical levels of surface antigens such as CD90, CD44, CD105 and CD73. The present immunophenotyping pattern of MSCs derived from umbilical cord and human heart were found to be consistent with the reports of other groups (Hoogduijn et al 2007;Park et al 2007;Bai et al 2007). In addition, ) between experimental groups.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Many subsequent studies have demonstrated that, umbilical cord and heart derived MSCs expressed identical levels of surface antigens such as CD90, CD44, CD105 and CD73. The present immunophenotyping pattern of MSCs derived from umbilical cord and human heart were found to be consistent with the reports of other groups (Hoogduijn et al 2007;Park et al 2007;Bai et al 2007). In addition, ) between experimental groups.…”
Section: Discussionsupporting
confidence: 92%
“…As well, the presence of Na? channel is responsible for inward sodium current (Bai et al 2007;Park et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain edema formation and BBB (blood-brain barrier) disruption, caused by both hematomal and peri-hematomal injuries, have also been reported to be an important component of brain injury after ICH [7][8][9][10][11][12]. Mesenchymal stem cells generated from murine or human adipose tissues have been well documented [13][14][15][16][17][18][19][20][21][22] and have been named as adipose-derived stem cells [14,15,19,20], adipose-derived adult stem cells [21], adipose derived stromal cells [16], adipose derived mesenchymal stem cells [18], adipose tissuederived stem cells [13], and adipose tissue stromal cells [17]. Systemic transplantation of human adipose-derived stem cells to attenuate cerebral inflammation and to facilitate motion recovery of rats from cerebral degeneration induced by ICH has been attempted [23].…”
Section: Introductionmentioning
confidence: 99%